Arthroscopic arthrolysis of posttraumatic and non-traumatic elbow stiffness offers comparable clinical outcomes - Saroj Rai (BMC Musculoskeletal Disorders, 2019)
Abstract Background Primary purpose of this study is to compare the clinical outcomes of patients undergoing arthroscopic arthrolysis in posttraumatic and non-traumatic elbow stiffness. Secondary aims are to compare the level of satisfaction and complications. Methods We retrospectively evaluated the patients undergoing arthroscopic elbow arthrolysis between January 2008 and September 2015 and have completed a minimum 2-year follow-up. Total of 141 patients (male = 90; female = 51) with 143 elbows (posttraumatic, n = 75; non-traumatic, n = 68) with an average age of 33 years were available for final evaluation. The average follow-up period was 44 months. We used the Mayo Elbow Performance Index (MEPI) score, range of motion (ROM), Visual Analogue Scale (VAS) to measure clinical outcomes. The level of satisfaction was measured by a self-constructed questionnaire. Results All parameters were significantly improved postoperatively (P < 0.01). However, statistically significant differences were not present in the rate of postoperative improvement of elbow ROM (P = 0.08) and MEPI (P = 0.21) in both groups. According to MEPI, 72(96%) elbows in posttraumatic and 60(88%) elbows in non-traumatic group were rated as good to excellent. No statistically significant differences were observed in the level of satisfaction (P = 0.76) and rate of complications (P = 0.91). Conclusions Arthroscopic arthrolysis is an effective tool and a good option for the treatment of patients with posttraumatic and non-traumatic elbow stiffness. The rate of elbow ROM and MEPI score improvements were significant and comparable postoperatively with a high level of patient’s satisfaction. However, postoperative rehabilitation is equally essential to maintain intraoperative elbow ROM, to attain optimal outcome and to prevent complications.